Chlamydomonas reinhardtii LHCSR1 and LHCSR3 proteins involved in photoprotective non-photochemical quenching have different quenching efficiency and different carotenoid affinity - Federico Perozeni (Nature Portfolio, 2020)
Abstract Microalgae are unicellular photosynthetic organisms considered as potential alternative sources for biomass, biofuels or high value products. However, their limited biomass productivity represents a bottleneck that needs to be overcome to meet the applicative potential of these organisms. One of the domestication targets for improving their productivity is the proper balance between photoprotection and light conversion for carbon fixation. In the model organism for green algae, Chlamydomonas reinhardtii, a photoprotective mechanism inducing thermal dissipation of absorbed light energy, called Non-photochemical quenching (NPQ), is activated even at relatively low irradiances, resulting in reduced photosynthetic efficiency. Two pigment binding proteins, LHCSR1 and LHCSR3, were previously reported as the main actors during NPQ induction in C. reinhardtii. While previous work characterized in detail the functional properties of LHCSR3, few information is available for the LHCSR1 subunit. Here, we investigated in vitro the functional properties of LHCSR1 and LHCSR3 subunits: despite high sequence identity, the latter resulted as a stronger quencher compared to the former, explaining its predominant role observed in vivo. Pigment analysis, deconvolution of absorption spectra and structural models of LHCSR1 and LHCR3 suggest that different quenching efficiency is related to a different occupancy of L2 carotenoid binding site.